CRISPR-Cas9 and its application potential in the brewing industry - Seibel, Katharina; De Mesmaeker, Mathias; Weiland, Florian (BrewingScience, 2022)
Over the last years, the CRISPR-Cas9 system has developed into the de facto standard gene modification technique in exploratory research. However, owing to its ease of usage and efficiency, CRISPR-Cas9 has also increasingly been exploited in the food industry while several applications have been reported for the brewing sector. Based on these developments, the present review aims at providing an overview of both the molecular background and function of the CRISPR-Cas9 system. This is followed by application examples of interest to the brewer. In the last part, the EU regulations and current scholarly discussion on genetically modified organisms are briefly summarized.